Combined impacts of land cover changes and large‐scale forcing on Southern California summer daily maximum temperatures. Issue 18 (21st September 2015) - Sequera, Pedro; González, Jorge E.; McDonald, Kyle; Bornstein, Robert; Comarazamy, Daniel
Abstract: California near‐surface air temperatures are influenced by large‐scale, regional and local factors. In that sense, a numerical model experiment was carried out to analyze the contribution of large‐scale (changes in atmospheric and oceanic conditions) and regional (increased urbanization) factors on the observed California South Coast Air Basin regional summer daily maximum temperature warming pattern from 1950 to 2013. The simulations were performed with past (1950–1954) and present (2009–2013) land cover and climate conditions. The past land cover was derived from historical digital maps, and the present land cover was updated with high‐resolution airborne remote sensing data. Results show that both factors contribute to the total change in daily maximum temperatures. Changes due to large‐scale climate conditions dominate in coastal (due to warming sea surface temperatures) and nonurban regions, while changes due to urbanization have an impact mainly in urban areas, especially inland where large‐scale warming weakens. Increased urbanization has also reduced sea‐breeze intensity due to changes in surface roughness. The model was able to reproduce the regional observed warming pattern, as it incorporates urban heat island effects, otherwise underestimated by large‐scale climate change only. Key Points: California surface temperatures are influenced by large‐scale and local factors Large‐scale climate changes dominate in coastal and nonurban regions Climate changes due to urbanization have an impact mainly in urban areas